Ações afirmativas e permanência no ensino superior: o caso de uma Instituição Federal de Ensino Superior em Minas Gerais - Brasil - de Almeida Santos , Álisson (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This article presents a debate regarding affirmative actions in getting into University and the challenges related to the permanence of students in the institution. It concerns an analysis about Universidade Federal de Juiz de Fora, completed through a qualitative research. It was observed that the student assistance policies have been emphasizing the financial aspect. Although it‟s important to combat socioeconomic inequalities, the observed environment points to the requirement of amplification of those policies.